Perception of the nursing team of an oncopediatric intensive care unit in the face of the terminality of life process (Research, Society and Development, 2021)
Objective: to understand the perception of the nursing team of an oncopediatric intensive care unit about the care for children and adolescents in the process of terminally ill life and to identify the difficulties encountered in approaching this clientele. Methodology: this is a descriptive study with a qualitative approach carried out in an Oncopediatric Intensive Care Unit of a hospital in the city of Rio de Janeiro. The instrument used for data collection was a semi-structured interview, composed of questions to characterize the participants and about the perception of nursing professionals about the topic in question. For data analysis, the content analysis technique was used, following the criteria proposed by Bardin. Results: 17 professionals from the nursing team participated, being 08 nurses and 09 technicians. The age range varied between 30 and 50 years of age, the majority being female. In the analysis, two categories were selected: 1) Understanding of nursing professionals about the condition of terminality; 2) Difficulties and the unpreparedness of the nursing team in the face of terminality. Conclusion: some professionals reported a lack of theoretical and practical knowledge about death, which indicates a knowledge gap in the training process. In addition, some were also very sensitive in relation to the theme, mainly because they are children. Even though these professionals know that death is part of their daily work, many consider themselves unprepared for this outcome.